Providing a Model for Developing the Entrepreneurial Capacity of the Young Generation of the Country in the Context of Curriculum Planning of the University - Somayeh Gharagozloo; Faezeh Nateghi; Mahnaz Jalalvandi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The purpose of this study was to provide a model for developing the entrepreneurial ability of the young generation in the context of higher education curriculum planning. The present study was developmental and qualitatively based on the data method of the Glaser Foundation. The statistical population in the study background consisted of all available domestic and foreign theoretical and research texts, related references and upstream documents of the education system of the Islamic Republic of Iran. The sampling method of this population was purposeful. There were curriculum and entrepreneurship which were selected by the method of snowball and theoretically saturated. The results showed that in the research background section, 46 components were extracted in the form of 8 factors and in the interview with experts’ section, and 71 components were extracted in the form of 12 factors. Similar to the elimination and final cases, which included 100 components in the form of 12 factors were extracted in the causal conditions of factors such as creativity and innovation, leadership, entrepreneurial experience and training, as well as in the intervention of five factors of teamwork, perseverance, risk-taking, independence and positive thinking. In the context of the three main factors of familiarity with the industry, the characteristics of the university and the support and infrastructure affecting the curriculum model were identified and determined based on entrepreneurial indicators.